1991
DOI: 10.1200/jco.1991.9.11.1967
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical modulation of fluorouracil with leucovorin: confirmatory evidence of improved therapeutic efficacy in advanced colorectal cancer.

Abstract: In a previous study (J Clin Oncol 7:1407-1417, 1989), we identified two dosage administration schedules of fluorouracil (5FU) combined with leucovorin that were superior to single-agent 5FU for the treatment of advanced colorectal cancer. In this same study, a regimen of 5FU plus high-dose methotrexate (MTX) demonstrated a suggestive advantage over 5FU alone. To permit a more definitive comparison, we have extended our evaluation of these three regimens to involve an additional 259 patients. In all, 457 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
96
4
8

Year Published

1995
1995
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(112 citation statements)
references
References 5 publications
4
96
4
8
Order By: Relevance
“…2 Clinical studies have clearly demonstrated the interest of this association allowing improved TS inhibition. 3 Despite the improved response rates with the addition of oxaliplatin or irinotecan, 5-FU remains a major drug in treatment of CRC. 4 However, many questions persist such as: how can we enhance the response rate and efficacy in terms of survival?…”
Section: Introductionmentioning
confidence: 99%
“…2 Clinical studies have clearly demonstrated the interest of this association allowing improved TS inhibition. 3 Despite the improved response rates with the addition of oxaliplatin or irinotecan, 5-FU remains a major drug in treatment of CRC. 4 However, many questions persist such as: how can we enhance the response rate and efficacy in terms of survival?…”
Section: Introductionmentioning
confidence: 99%
“…The response rate to single-agent 5-FU in bolus form is only 11% (Advanced Colorectal Meta-Analysis Report, 1992), but this can be improved when 5-FU is given in combination with folinic acid (Poon et al, 1991), albeit at the expense of increased toxicity.…”
mentioning
confidence: 99%
“…The most optimistic studies testing 5-FU for first-line in colo-rectal carcinoma reported overall response rate lower than 15%, with a median survival of 12 -18 months. Clinical evidence suggests that the use of protracted intravenous infusion of 5-FU may be more efficacious and better tolerated than bolus dosing (Cancer, 1998), and that modulation of 5-FU may lead to higher response rates (Poon et al, 1989(Poon et al, , 1991. Oxaliplatin is a novel diaminocyclohexane platinum agent that mainly acts by causing inter-and intrastrand DNA crosslinks (Mathe et al, 1989;Soulie et al, 1997;Wiseman et al, 1999;Culy et al, 2000).…”
Section: Discussionmentioning
confidence: 99%